Detection and Identification of Jaagsiekte Retrovirus Associated With Sheep Pulmonary Adenomatosis - Ze, Zhu (2002)
Sheep pulmonary adenomatosis (SPA) or jaagsiekte is a neoplastic disease of sheep, caused by jaagsiekte retrovirus (JSRV) infection in the lungs. In Malaysia, the disease was first observed in 1993, involving mainly the purebred imported sheep and their crossbreeds, and a long time after the first importation of sheep from Australia into Malaysia in 1987. The JSRV was found to transform the alveolar type II cells in the lungs of sheep to become neoplastic cuboidal cells arranged in acinar or papillary patterns. The neoplastic cells were found to cover the entire alveolar wall with numerous macrophages filling the affected alveoli particularly the alveoli surrounding the neoplastic area. The affected lung tissue and lung fluid were successfully processed to partially purify the materials before the JSRV was successfully detected under the electron microscopy from several local SPA-affected sheep, which showed clinical signs typical of sheep pulmonary adenomatosis. Following the detection of JSRV under the electron microscopy, the virus was later confirmed as the JSRV by using the reverse-transcription polymerase chain reaction (RT-PCR) technique at the viral nucleic acid level. The study. therefore, confirmed that JSRV is present in Malaysia and thus, should be considered in the diagnosis of sheep diseases and in controlling the spread of contagious diseases such as sheep pulmonary adenomatosis. Following the confirmation of the jaagsiekte retrovirus in Malaysia, a RTPCR diagnostic method was developed based on the U3 gene of the retrovirus. The method was able to identify the presence of retrovirus in the peripheral blood of sheep with and without clinical signs of sheep pulmonary adenomatosis. Thus, the technique can be used to identifY subclinically infected animals for culling.